Myotonic dystrophy: diagnosis, management and new therapies. - Turner, C; Hilton-Jones, D (2014)
PURPOSE OF REVIEW: Myotonic dystrophies type 1 and type 2 are progressive multisystem genetic disorders with clinical and genetic features in common. Myotonic dystrophy type 1 is the most prevalent muscular dystrophy in adults and has a wide phenotypic spectrum. The average age of death in myotonic dystrophy type 1 is in the fifth decade. In comparison, myotonic dystrophy type 2 tends to cause a milder phenotype with later onset of symptoms and is less common than myotonic dystrophy type 1. Historically, patients with myotonic dystrophy type 1 have not received the medical and social input they need to maximize their quality and quantity of life. This review describes the improved understanding in the molecular and clinical features of myotonic dystrophy type 1 as well as the screening of clinical complications and their management. We will also discuss new potential genetic treatments. RECENT FINDINGS: An active approach to screening and management of myotonic dystrophies type 1 and type 2 requires a multidisciplinary medical, rehabilitative and social team. This process will probably improve morbidity and mortality for patients. Genetic treatments have been successfully used in in-vitro and animal models to reverse the physiological, histopathological and transcriptomic features. SUMMARY: Molecular therapeutics for myotonic dystrophy will probably bridge the translational gap between bench and bedside in the near future. There will still be a requirement for clinical screening of patients with myotonic dystrophy with proactive and systematic management of complications.